The Role of Age and Exposure in English Vowel Perception and Production among Native Swahili Speakers - Rose Acen Upor; Joseph J. Olomy (Master Program in Linguistics, Diponegoro University, 2021)
Vowel perceptual studies in Foreign Language Acquisition (FLA) settings where L1 is dominant are generally scarce. The aim of this study, therefore, is to explore the role of the age and exposure factors in the perception and production of English vowels [ɑ-ɜ; æ-ɑ; i-ɪ] by the native Swahili speakers whose exposure to the English language is through formal instruction in a predominantly FLA situation. The participants (n=40) were classified into two groups: Young learners and adult learners. Using Flege’s Speech Learning Model (SLM), we administered a vowel perception test, and a vowel production exercise. The results confirm that adult learners have an edge over younger learners whereby the former exhibited greater accuracy in determining vowel contrasts and production than the latter. Although both groups shared common difficulties in discriminating the vowel sounds, adult learners had recourse to their prolonged exposure and ingeniously used previously acquired knowledge and skills in sentence structure and meaning to aid discrimination in comparison to the younger learners. Finally, the study supports the SLM contention that adults retain capacities to acquire L1 to perceive the properties of L2 speech sounds and establish new phonetic categories.